Increased endothelial progenitor cells with age and grade of malignancy in astrocytic glioma patients - Das, Priscilla; Naing, Nyi Nyi; Wan Abdul Jamil, Wan Arfah Nadiah; Khin, Ohnmar Naing @ Noor Jan; Kueh, Yee Cheng; Rasalingam, Kantha (Universiti Putra Malaysia Press, 2018)
Astrocytic gliomas are the most common primary brain tumours that originated from human glial cells. The tumours rely upon endothelial progenitor cells (EPCs) for neoangiogenesis. This study aimed to investigate the association between tissue resident EPCs in a brain tumour and normal adjacent tissue in relation to age and grade of astrocytic glioma. Astrocytic glioma patients (n=22), grade I to grade IV were consented from Hospital Universiti Sains Malaysia. Brain tumour tissue and normal adjacent brain tissue samples were obtained from each patient during surgery. The EPCs were stained with CD133+ and VEGFR-2+ markers. The tissue residents EPCs for each sample were determined using the immunofluorescence microscopy method. The age of the patients increased by disease severity in the following order (Grade I: 21.33±20.79 years) < (Grade II: 46.50±0.707 years) < (Grade III: 47.38±11.95 years) < (Grade IV: 48.44 ±10.66 years). The EPCs in brain tumour correlated significantly with the age of the patients with positive correlation (Spearman's rho correlation test, r=0.52; p=0.013). The tissue resident EPCs in the brain tumour (median=0.40, IqR=0.59) were significantly higher compared with the adjacent normal brain (median=0.067, IqR=0.29) (Wilcoxon Signed-Rank Test, Z stat=-3.587, p<0.001). Higher tissue resident EPCs were found in high grade (III & IV) glioma compared with EPCs in low grade (I & II) glioma (median=0.61, IqR=0.70 vs. median=0.26, IqR=0.30; z=-1.763 p=0.078). This study showed increased EPCs with age and grade of malignancy in astrocytic glioma patients. Therefore, targeting EPCs in gliomas based on tumour grade malignancy and age of the patients might be useful in effective treatment of astrocytic glioma.